Pengaruh Disiplin Kerja , Motivasi Kerja, Pengembangan Karir dan Stres Kerja Karyawan terhadap Kepuasan Kerja Karyawan pada PT. Asuransi Kredit Indonesia Cabang Kediri - Mella Vebianti; Bambang Suwarsono; Brahma Wahyu Kurniawan (Global Leadership Organizational Research in Management, 2025)
Considerations including work discipline, motivation, career growth possibilities, and stress may help us understand how satisfied PT. Asuransi Kredit Indonesia Kediri Branch employees are with their jobs. Using a non-probability selection strategy, this quantitative research selects a representative sample of 34 workers. Dalam SPSS versi 25, kami memeriksa kenormalan, autokorelasi, heteroskedastisitas, multikolinearitas, dan ketergantungan; kami juga memeriksa validitas dan reliabilitas. Selain itu, analisis statistik berikut dilakukan: uji-t, uji-F, analisis regresi linier berganda, dan perhitungan koefisien determinasi R². Work discipline significantly and positively affects job satisfaction, according to the study's findings (t significance value of 0.000, less than 0.05). With a t-statistic of 0.000 <0.05, it is clear that work motivation significantly impacts job satisfaction. Likewise, possibilities for professional advancement significantly impact work satisfaction in a favorable way, as shown by a t-value of 0.000 < 0.05. Also, with a t-value of 0.040 < 0.05, it is shown that work stress is positively and significantly correlated with job satisfaction. Job satisfaction is impacted by a combination of work ethic, motivation, and professional progress.